The effects of adherence to recommended antenatal services on adverse pregnancy outcomes in Northwest Ethiopia: multilevel and propensity score matching (PSM) modeling - Zelka, Muluwas Amentie; Yalew, Alemayehu Worku; Debelew, Gurmesa Tura (Frontiers in Global Women's Health, 2023)
Introduction Adverse pregnancy outcomes are a personal and social crisis caused by easily preventable pregnancy-related problems. Despite that, studies on the effectiveness of adherence to the continuity of antenatal care (ANC) services are scarce. Therefore, this study aims to determine the effectiveness of the continuity of ANC services and the determinants of adverse pregnancy outcomes. Methods A prospective follow-up study design was conducted from March 2020 to January 2021 in Northwest Ethiopia among randomly selected study subjects. Data were collected by trained data collectors using pre-tested structured questionnaires and analyzed using STATA Software version 14. A multilevel regression model was used to identify determinant factors, whereas the propensity score matching (PSM) model was used to look at the effectiveness of adherence to ANC services on adverse pregnancy outcomes. Results Among 2,198 study participants, 26.8% had adverse pregnancy outcomes, with 95% CI: 24.9–28.7 [abortion (6.1%; 95% CI: 5.1–7.1), low birth weight (11.5%; 95% CI: 10.2–12.9), and preterm birth (10.9; 95% CI: 9.6–12.3)]. Determinant factors were iron-folic acid supplementation (AOR = 0.52; 95% CI: 0.41, 0.68), delayed initiation of ANC visits at 4–6 months (AOR = 0.5; 95% CI: 0.32, 0.8), initiation of ANC visits after 6 months (AOR = 0.2; 95% CI: 0.06, 0.66), received four ANC visits (AOR = 0.36; 95% CI: 0.24, 0.49), an average time of rupture of the amniotic membrane of between 1 and 12 h (AOR = 0.66; 95% CI: 0.45, 0.97), and pregnancy-related problems (AOR = 1.89; 95% CI: 1.24, 2.9). As a treatment effect, completion of a continuum of visit-based ANC (ATET; β = −0.1, 95% CI: −0.15, −0.05), and continuum of care via space dimension (ATET; β = −0.11, 95% CI: −0.15, −0.07) were statistically significant on the reduction of adverse pregnancy outcomes. Conclusion In the study area, the rate of adverse pregnancy outcomes was high. Even though adherence to the continuity of ANC services via time and space dimensions is effective in the prevention of adverse pregnancy outcomes, programmatically important factors were also detected. Therefore, key strategies for promoting the uptake of antenatal services and strengthening iron-folic acid supplementation are strongly recommended.